Numerical simulation of the planetary boundary layer in Iperó, SP-Brazil - Scolar, J. [UNESP]; Neto, E. S.C. [UNESP]; De Oliveira, A. P.; Soares, J. (My University, 2000)
One-dimensional second order numerical model coupled with surface budget energy prognostic equations is used to simulate the planetary boundary layer (PBL) in the region of Iperó-SP. Model results indicate that vertical turbulent sensible and latent heat fluxes decrease upwards quasi-linearly from a maximum positive value at the surface. This implies that heat and humidity are transported from the ground surface into the higher atmosphere. The mechanical turbulent flux at night is very small and the thermal flux nearly ceases in all PBL vertical extension. Consequently, temperature and humidity mean vertical profiles are better simulated during the daylight period. On the other hand, the surface fluxes and simulated radiation budget are in very good agreement with the observed values. Therefore, the inclusion of the surface energy budget equation permits a significant improvement on the air near surface daily cycle temperature simulation.
Simulação numérica da camada limite planetária na região de Iperó, SP-Brasil
Keywords: Latent and Sensible Heat Fluxes; Planetary Boundary Layer; Surface Temperature; Turbulent Fluxes